Development of a rapid and highly accurate diagnostic test for detecting Theileria equi in horses using recombinase polymerase amplification (RPA) combined with nucleic acid lateral flow immunoassay - Al-khafaji, A.; Alsultan, A.; Alsallami, D. (Polish Journal of Veterinary Sciences, 2026)
Equine piroplasmosis (EP) is a protozoan disease in horses, mainly caused by Theileria equi, and is associated with non-specific signs such as fever, anemia, and edema. The lack of specific clinical signs, coupled with the high prevalence of carrier horses, highlights the critical need for a rapid and highly accurate diagnostic test for the detection of Theileria equi. Existing methods, including molecular, serological, and microscopic techniques, require specialized equipment, skilled personnel, and considerable time. The current study aims to develop a rapid and accurate assay for the detection of Theileria equi in horses by using pre-labeled DNA in combination with recombinase polymerase amplification (RPA) and a lateral flow device (LFD). The proposed assay was evaluated in terms of time efficiency, sensitivity and specificity. Of the 30 samples tested, 23 were positive for Theileria equi, with no false positives observed. Moreover, the assay demonstrated a detection limit as low as 5 ng per microliter of input DNA, and the entire process from sample preparation to result interpretation was completed within 25 minutes without the need for specialized equipment. The findings demonstrate that the proposed assay exhibits 100% specificity, high sensitivity, and strong potential for clinical application. However, further studies are required to optimize the assay for direct pathogen detection from samples, eliminating the need for DNA extraction.